(untitled) (Itinerarios Educativos, 2024)
In the contemporary world we experience the deepening of a regime of inequalities installed for decades. Educational institutions, as consecutive of the social, are not exempt from these situations; therefore we decided to take some fragments of reality to carry out an interdisciplinary project linked to teaching and commitment to the community from our place, the school. It involves actors who wish to participate and go through two higher–level careers of the Escuela Normal Superior Nº 6 «Vicente López y Planes» —ENS Nº 6 of the Ciudad Autónoma de Buenos Aires— Initial Education Teachers (PEI) and Higher Technician in Clothing Production (TSPI). An inter–cathedra project is born in which teachers weave warp and weft with and together with our students. From the PEI, lullabies, song lyrics that lull children to sleep, are selected and worked on to accompany first skin clothes made by TSPI students that are then donated to Hospitals in the Ciudad Autónoma de Buenos Aires.